Evaluation of elastic bands for lower extremity resistance training in adults with and without musculo‐skeletal pain. Issue 5 (20th February 2014) - Sundstrup, E.; Jakobsen, M. D.; Andersen, C. H.; Bandholm, T.; Thorborg, K.; Zebis, M. K.; Andersen, L. L.
<x xml:space="preserve">Abstract</x> Therapists commonly use elastic bands in resistance exercises during rehabilitation of smaller muscles, such as in the shoulder. However, the effectiveness has not yet been investigated for larger muscle groups. This study investigates muscle activity during lower extremity exercises. Electromyographic (EMG) activity of 10 muscles was measured in 24 women and 18 men during lunges with elastic resistance, lunges with dumbbells, and unilateral leg press in machine using 10 repetition maximum loadings, and normalized to maximal voluntary isometric contraction EMG. Lunges with dumbbells and leg press showed higher activity than lunges with elastic resistance for the vasti and rectus femoris (P < 0.01), whereas lunges with elastic resistance showed higher activity of gluteus maximus, hamstrings, and erector spinae (P < 0.01). Gender, age, and pain in the knees and hip did not influence these findings. However, pain in the lower back decreased muscular activity of the gluteus maximus and vastus medialis (P < 0.01). Lunges with elastic resistance induce high levels of muscle activity in all the large muscle groups at the hip, knee, and back. Importantly, the efficiency of these exercises was equally high regardless of gender, age, and pain in the knees and hip, whereas pain in the lower back led to altered activation strategies.